Hepatic factor may not originate from hepatocytes - Merbach, Monica; Ramchandran, Ramani; Spearman, Andrew D. (Frontiers in Cardiovascular Medicine, 2022)
Pulmonary arteriovenous malformations (PAVMs) develop universally in patients with univentricular congenital heart disease. They are believed to form due to lack of an unidentified factor from hepatocytes that perfuses the lungs to maintain vascular homeostasis and prevent PAVM formation. This unidentified factor is termed hepatic factor; however, the identity, mechanism, and origin of hepatic factor are unknown. Several hepatic factor candidates have been previously proposed, but few data are available to support previous hypotheses. Recent data showed that soluble vascular endothelial growth factor receptor 1 (sVEGFR1) is enriched in hepatic vein blood and may be a potential hepatic factor candidate. We used imaging and molecular approaches with wild-type mice to determine whether sVEGFR1 originates from hepatocytes in the liver. To our surprise, we identified that sVEGFR1 is negligibly expressed by hepatocytes but is robustly expressed by the non-parenchymal cell population of the liver. This suggests that hepatic factor may not originate from hepatocytes and alternative hypotheses should be considered. We believe it is necessary to consider hepatic factor candidates more broadly to finally identify hepatic factor and develop targeted therapies for CHD-associated PAVMs.